Traitor - McCrina, Amanda, 1990- (Square Fish, 2022)
In Poland, 1944, the Soviets have liberated Lwów from Germany, but the city remains a battleground as resistance and insurgent armies clash between loyalty to Ukraine or loyalty to Poland. Seventeen-year-old Tolya Korolenko is half of each side, so he joins the Red Army to stay alive and fed. Then, he not-so-accidentally shots his superior political officer and is taken in by Ukrainian freedom fighters, whom he isn't sure he can trust. Then, he finds out these freedom fighters have secrets they would kill to keep safe.